Satellite tracking data on Malaysian green turtle migration - Liew, Hock-Chark; Chan, Eng-Heng; Luschi, Paolo; Papi, Floriano (1995)
Satellite telemetry has been used on green turtle (Chelonia mydas) females nesting in West Malaysia to study their migratory routes, behaviour during migration and homing after displacement. For three turtles the complete migratory journey was tracked, while another one was followed for part of the trip. The return path to the nesting beach following displacement of one of the turtles from 284 km was also tracked. All the useful localizations are reported, thus providing the basic information for further analysis. © 1995 Accademia nazionale dei Lincei.